Анализ схем управления гидропневмоагрегатов - Черкашенко, Михаил Владимирович; Вурье, Борис Александрович; Гринберг, Юрий Исаакович; Бондарева, Дарья Борисовна (НТУ "ХПИ", 2016)
Предлагается метод анализа схем гидропневмоагрегатов, позволяющий обнаружить и устранить имеющиеся ошибки при проектировании, в основном, связанные с противоречивостью входов, действующих между технологическими операциями, и "силовой борьбой" на исполнительных устройствах. Показана эффективность использования для анализа схем матрицы соответствий М. В. Черкашенко, размерность которой не зависит от числа входов и выходов, а лишь от числа переходов между технологическими операциями.

Method of analysis of hydropneumatic units control system schemes, allows to detectand eliminate the existing design errors, is offered. These errors are mainly related to the contradictory of inputs, occurring between the technological operations and "struggle of inputs" on executive devices. For correction the scheme of hydropneumatic units control system the matrix of conformities was used. The dimension of the matrix does not depend on number of inputs and outputs, and only from number of transitions between technological operations. Efficiency of use the matrix of conformities for analysis is shown.
Analysis of the hydropneumatic units management schemes
Keywords: синтез; системы управления; исполнительные устройства; технологические операции; synthesis; control system